Isolation of a full-length mouse cDNA clone coding for an immunologically distinct p53 molecule. - Wolf, D (1985)
Transfection of a cloned p53 gene into a p53 nonproducer Abelson murine leukemia virus-transformed cell line, L12, reconstituted p53 expression. The protein expressed in these cells was indistinguishable from that naturally expressed in p53 producer tumor cells. Conversely, p53 protein expressed in L12-derived clones that were established by transfection with a full-length p53 cDNA clone (pM8) exhibited a discrete immunological form. Immunoprecipitation of p53 with a panel of monoclonal anti-p53 antibodies showed that L12-derived clones that were transfected with the genomic p53 clone contained the same antigenic determinants as those found in the p53 protein expressed in tumor cells. These p53 proteins bound all monoclonal antibody types as well as the polyclonal anti-p53 tested. However, L12-derived clones established by transfection of the p53 cDNA clone (pM8) expressed a p53 protein that bound the RA3-2C2 and PAb200.47 anti-p53 monoclonal antibodies as well as polyclonal anti-p53 serum but totally lacked the antigenic receptor for the PAb122 and PAb421 monoclonal antibodies. The p53 proteins expressed by either genomic or cDNA p53 clones exhibited the same apparent molecular sizes and identical partial peptide maps. We suggest that transfection of the p53 gene induced expression of the entire group of the possible mRNA species, whereas cloned p53 cDNA (pM8) represented a single mRNA molecule that codes for a discrete species of p53 protein.